Low-pT e+ e- pair production in Au+Au collisions at √sNN=200 GeV and U+U collisions at √sNN=193 GeV at STAR - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review letters, 2018)
We report first measurements of e+e− pair production in the mass region 0.4<Mee<2.6 GeV/c2 at low transverse momentum (pT<0.15 GeV/c) in noncentral Au+Au collisions at √sNN=200 GeV and U+U collisions at √sNN=193 GeV. Significant enhancement factors, expressed as ratios of data over known hadronic contributions, are observed in the 40%-80% centrality of these collisions. The excess yields peak distinctly at low pT with a width (√⟨p2T⟩) between 40 and 60 MeV/c. The absolute cross section of the excess depends weakly on centrality, while those from a theoretical model calculation incorporating an in-medium broadened ρ spectral function and radiation from a quark gluon plasma or hadronic cocktail contributions increase dramatically with an increasing number of participant nucleons. Model calculations of photon-photon interactions generated by the initial projectile and target nuclei describe the observed excess yields but fail to reproduce the p2T distributions.